MOMO – V. Effelsberg, Swift, and Fermi study of the blazar and supermassive binary black hole candidate OJ 287 in a period of high activity. Issue 3 (24th March 2022) - Komossa, S; Grupe, D; Kraus, A; Gonzalez, A; Gallo, L C; Valtonen, M J; Laine, S; Krichbaum, T P; Gurwell, M A; Gómez, J L; Ciprini, S; Myserlis, I; et al.
ABSTRACT: We report results from our ongoing project MOMO (Multiwavelength Observations and Modelling of OJ 287). In this latest publication of a sequence, we combine our Swift UVOT–XRT and Effelsberg radio data (2.6–44 GHz) between 2019 and 2022.04 with public SMA data and gamma-ray data from the Fermi satellite. The observational epoch covers OJ 287 in a high state of activity from radio to X-rays. The epoch also covers two major events predicted by the binary supermassive black hole (SMBH) model of OJ 287. Spectral and timing analyses clearly establish: a new UV–optical minimum state in 2021 December at an epoch where the secondary SMBH is predicted to cross the disc surrounding the primary SMBH; an overall low level of gamma-ray activity in comparison to pre-2017 epochs; the presence of a remarkable, long-lasting UV–optical flare event of intermediate amplitude in 2020–2021; a high level of activity in the radio band with multiple flares; and particularly a bright, ongoing radio flare peaking in 2021 November that may be associated with a gamma-ray flare, the strongest in 6 yr. Several explanations for the UV–optical minimum state are explored, including the possibility that a secondary SMBH launches a temporary jet, but the observations are best explained by variability associated with the main jet.